Abundance and distribution of macro- and micro-plastics at three different habitats along the Penang Coastline in the Northern Straits of Malacca - Er, Vin Lim; Izam, Nur Izzati Izyan; Nilamani, Nithiyaa; Razalli, Norhanis Mohd; Zanuri, Norlaila Mohd; Yasin, Zulfigar; Shau, Aileen Hwai Tan; Shoufeng, Zhang; Hongjun, Li (Faculty of Science, Ramkhamhaeng University, 2020)
The abundance and distribution of Macro- (> 2.5 cm) and microplastics (1-5 mm) at three different habitats were documented. Particle size analysis on the sediment of each habitat were carried out to characterize the habitat. Macroplastics and microplastics were found at all study sites. Macroplastics were found only at the high tide line. Packaging, electrical and electronic, household, construction, agriculture and others plastics market sector were found. The highest amount of macroplastics were found at Pulau Betong (mudflat) which was 20.25 g/m2. Fragment, film, foam, and filament type of microplastics were found. The highest average number of microplastics were found at the high tide line of all study sites. The highest total number of microplastics among the study sites found during the sampling time and within the quadrats employed was 72 items at Teluk Aling (fine sandy beach). The source of plastics pollution was from local activities and transportation of debris from other places by oceanic current and wind.